1976
DOI: 10.1083/jcb.68.3.629
|View full text |Cite
|
Sign up to set email alerts
|

Reversibility of cell surface label rearrangement.

Abstract: Cell surface labeling can cause rearrangements of randomly distributed membrane components. Removal of the label bound to the cell surface allows the membrane components to return to their original random distribution, demonstrating that label is necessary to maintain as well as to induce rearrangements. With scanning electron microscopy, the rearrangement of concanavalin A (con A) and ricin binding sites on LA-9 cells has been followed by means of hemocyanin, a visual label. The removal of con A from its bind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
11
0

Year Published

1978
1978
1981
1981

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(15 citation statements)
references
References 51 publications
(94 reference statements)
4
11
0
Order By: Relevance
“…Again lanes were washed sequentially in incubation buffer and BSA (2 x 1 h each). Incubation with l"I-protein A, prepared by the chloramine-T procedure (12), approximately 5 x 106 cpm in 5 ml of BSA, proceeded for a period of 6 to 18 h. Lanes were washed as described above, dried on filter paper, and exposed to Kodak No-Screen X-ray film for 1 to 6 days.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Again lanes were washed sequentially in incubation buffer and BSA (2 x 1 h each). Incubation with l"I-protein A, prepared by the chloramine-T procedure (12), approximately 5 x 106 cpm in 5 ml of BSA, proceeded for a period of 6 to 18 h. Lanes were washed as described above, dried on filter paper, and exposed to Kodak No-Screen X-ray film for 1 to 6 days.…”
Section: Methodsmentioning
confidence: 99%
“…Some progress has been made by labeling membrane components. The specificity of lectin binding, for example, has allowed investigators to localize glycoprotein in cell membranes and to study mechanisms of lateral mobility of membrane components (6,34). Immunological approaches have been successful in identifying receptor sites on membranes (29), but studies with antisera to intact membranes have failed to produce much useful information concerning molecular mechanisms of membrane-associated phenomena.…”
mentioning
confidence: 99%
“…WGA-microspheres, however, are maintained in a dense uniform array on the cell surface. Brown and Revel [6] have also reported that when cultured mouse L cells were continuously labeled with ricin-hemocyanin markers, a homogeneous pattern of label was observed; cells continuously labeled with Con A-hemocyanin displayed a heterogeneous labeling pattern. This difference in the pattern of redistribution of Con A sites and WGA or RCA…”
Section: Ts: Somentioning
confidence: 92%
“…Con A possesses mitogenic responses toward some classes of lymphocytes [34] and alters the morphology and differentiation pattern o f 3 number of cell types. In particular, it has been reported that Con A reverses differentiation in neuroblastoma cells [35], causes a rounding up and clustering of microvilli on Dictyostelium cells [5] , and inhibits ruffling activity on L cells [6] . WGA and RCA.…”
Section: Ts:503mentioning
confidence: 99%
See 1 more Smart Citation